Effects of Different Compost Types on the Growth and Yield of Amaranth (Amaranthus spp.) - Akhmad Hamam Nasirudin; Rennanti Lunnadiyah Aprilia (Asosiasi Dosen Muda Indonesia, 2026)
Vegetable amaranth is a fast-growing leafy vegetable with high nutritional value and strong potential for sustainable cultivation. Livestock-manure compost is increasingly used as an environmentally friendly nutrient source to improve crop growth and reduce dependence on inorganic fertilizers. Objective: This study aimed to evaluate the effects of different livestock-manure composts on the growth and yield of several vegetable amaranth varieties under polybag cultivation and to identify the most effective treatment combination. Method: The study was conducted in Jatisari Village, Kebumen District, Central Java, Indonesia, from January to February 2026. A quantitative experimental approach was applied using a 3 × 4 factorial randomized complete block design with nine effective blocks. The first factor was compost type, namely chicken-, goat-, and cow-manure compost, while the second factor was amaranth variety, namely green, uproot, red, and batik amaranth. Data were collected through direct plant measurements and analyzed using ANOVA followed by DMRT at the 5% level. Findings: The interaction between compost type and variety significantly affected plant height, number of leaves, leaf area, fresh plant weight, dry plant weight, fresh root weight, and dry root weight, but did not significantly affect root length. The best overall performance was obtained from cow-manure compost combined with green amaranth (P3V1). Implications: Cow-manure compost is a promising organic input for improving vegetable amaranth productivity under polybag cultivation. Originality: This study provides comparative evidence on three livestock-manure composts across four amaranth varieties under local cultivation conditions.